Development of the tourism industry based on regional competitiveness, Palopo City, South Sulawesi - Syaiful Bachri; Abubakar Betan; Lorensius Lonik (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The results achieved are that there are important aspects that must be considered in an effort to develop tourism in Palopo City . Regional cooperation with surrounding regions, to become a regional tour major in Palopo City and Developing Center of Culture as a center of Excellence for the development of culture specifically Palopo To ensure the sustainability of travel as the basis of development economics in Palopo, community involvement and industry players travel very needed. Tourism infrastructure is still an obstacle to tourism development in Palopo City. The development of tourism must be part of the Medium Term Development Plan (RPMJ) and in lowering the Plan of Development Annual which is integrated with the development of the other.